Medication Safety: A Need to Relook at Double-Checking Medicines? - Gek Phin Chua; Kim Hua Lee; Gemma Diente Peralta; John Heng Chi Lim (Elsevier, 2019)
Objective: To present a structured evaluation process that provides evidence that the single-checking (SC) system is not only a viable option in reducing medication errors, but also has the added advantage of increasing staff satisfaction. Methods: The structured evaluation involved one work improvement process and conducting a survey establishing registered nurses' (RNs') attitude toward SC of medicines. The survey questionnaire included 12 questions with a 5-point Likert scale. Results: In spite of the increased number of patients, the number of medication errors actually reduced (P < 0.001; two-sample test of proportions) with the implementation of SC of medication for competent and experienced staff. A survey was conducted to establish RNs' attitudes toward SC of medicines 3 years post SC implementation. RNs viewed the single-nurse checking protocol positively. In particular, the nurses considered single-nurse checking as an encouragement to update their drug knowledge and as a time-saving measure, enhancing the quality of patient care. Nonetheless, they also expressed concerns on single-nurse checking. Conclusions: The findings provide evidence that SC system is a viable way to reducing medication errors and also confer the added advantage of staff satisfaction. Assuring quality and safety involves the need to challenge the status quo based on revealed evidence.